ROLE OF MANAGEMENT ACCOUNTING OF THE RAILWAYS - E. Sedova; V. Kramarenko (Вестник университета)
The article explores practical approaches to the optimization of management accounting venture railway industry through the introduction of an automated system. The necessity of improving the management accounting system, which will lead to the optimization of the organization of warehouse activities and all transport companies.